Response of Broiler Chicks to Graded Levels of Alphamune G Supplementation - Bolu, S.A.; Ojo, V.; Oyeleke, B.A.; Ajiboye, A.O.; Sambo, A. Baa; Oluyemi, O. (International Journal of Poultry Science, 2008)
A study was conducted on 120 day-old broiler chicks fed graded levels of Alphamune G (0.00, 0.04, 0.05 and 0.06%) in a Completely Randomized Design. The experiment was conducted for 8 weeks. Feed intake and weight gain were significantly influenced (p0.05) except in PCV value where 0.04% inclusion of Alphamune had significantly lower value (31.00%). However all values fall within the normal range. Histological studies revealed morphological changes in broilers fed Alphamune G supplemented diet viz- a-viz the control diet. Alphamune G at 0.04% inclusion in diets of broilers may help improve performance.